Nematodes as model organisms - Glazer, Itamar; Shapiro-Ilan, David I.; Sternberg, Paul W. (CAB International, 2022)
"Nematodes, especially Caenorhabditis elegans have been used as a model for research in molecular biology since the 1960's. This is a much-needed update on research on fundamental processes in areas such as genetics, developmental biology, nutrition, toxicology, ecology, pharmacology and medicine"--